RESEARCH OF QUAIL MEAT FOR THE PRESENCE OF HEAVY METALS AND PESTICIDES WHEN ADDING A MINERAL FEED ADDITIVE TO THEIR DIET - Taiguzin, R. S.; Montayeva, N. S. (Ғылым және білім=Наука и образование=Science and education. - 2021. - № 4 (65)., 2021)
The article presents the results of laboratory tests for the presence of heavy metals and pesticides when adding a mineral feed additive to the diet of birds. The relevance of the study is related to the cultivation of healthy and highly productive quails in order to ensure food security of the Republic of Kazakhstan. The conducted studies of meat to assess the indicators for the presence of heavy metals and pesticides for the purpose of using a mineral feed additive on experimental birds (quails) allowed us to obtain the following results: pesticides in all samples - less than 0.005 mg/kg, mercury and arsenic - less than 0.0002, the presence of lead in four samples did not reach critical indicators. A comprehensive analysis of the results obtained on the basis of scientific and experimental studies of meat to assess the indicators for the presence of heavy metals and pesticides showed the harmlessness of mineral feed additives when used in the diet of quails. В статье представлены результаты лабораторных исследований на наличие тяжелых металлов и пестицидов при добавлении минеральной кормовой добавки в рацион птиц. Актуальность исследования связана с выращиванием здоровых и высокопродуктивных перепелов в целях обеспечения продовольственной безопасности Республики Казахстан. Проведенные исследования мяса для оценки показателей на наличие тяжелых металлов и пестицидов с целью применения минеральной кормовой добавки на подопытных птицах (перепелах) позволили получить следующие результаты: пестициды во всех образцах - менее 0,005 мг/кг, ртуть и мышьяк - менее 0,0002, наличие свинца в четырех образцах не достигло критических показателей. Комплексный анализ результатов, полученных на основе научно-экспериментальных исследований мяса по оценке показателей на наличие тяжелых металлов и пестицидов, показал безвредность минеральной кормовой добавки при использовании в рационе перепелов.
Keywords: научный журнал; отечественное издание; периодическое издание; журнал коксон; heavy metals; pesticides; flasks; quail; opoka; минеральные кормовые добавки; питание птиц; пестициды